The Occurence of Abbreviation in Indonesia Lawak klub (ILK) To Obtain Humor Effect - Setyowati, Hari (LANTERN (Journal on English Language, Culture and Literature), 2017)
ABSTRACT            Language is the core part that we need to build a communication among people. For many cases, language is dynamic so that its users can manipulate it to give a certain meaning, such as, Indonesian. Many abbreviations occurred are used for different purposes, for instance, a slogan of cities, a trend among teenagers and a humor. Indonesia Lawak Klub (ILK), as a parody show of television, proves how language can be manipulated to obtain humor effect.            The theories used are Morphology from Yule and Kridalaksana in order to analyze the data through word formation and to find out pattern of abbreviation used in ILK. In addition, the writer also shows why abbreviations can obtain the humor effect in this show.            The writer conducts the research by using a descriptive qualitative approach and random sampling. The data were taken from seven episodes of ILK broadcasted in April 2014. The analyzed sample data are 13 abbreviations from 10 conversations accomplished by varies of word formation processes.            The result of the research is the fact that most of abbreviations happened during ILK are formed by multiple processes. They mostly go through by borrowing and contraction. Besides, the humor that the speakers uttered can be mostly gained by contradictive.Keywords: abbreviation, word process, humor